Research on a rotational speed control strategy of the mandrel in a rotary steering system - Zhang Liancheng; Zhang Guibin; Spillian John (Open Physics, 2018)
Rotary steering systems are cutting-edge, intelligent oil drilling and steering equipment developed at the end of the twentieth century. The core function of the bit pointing rotary steering system is to control the eccentric shaft with bit pointing function to track the outer drill collar for reverse rotation [1]. When the relative speed thereof is offset, the mandrel tool face remains stationary, and the directive function of the drill bit is realized [2]. Therefore, it is important to precisely control mandrel rotational speed and make it follow the outer drill collar to conduct face-to-face rotation at all times. A double closed loop control method for realizing rotational speed loop and position loop through controlling mandrel rotational speed is proposed in this paper. Relative rotational speed of drill bit shaft (or mandrel) and drill collar of zero can be realized within the shortest time, thereby realizing rapid and precise rotational speed tracking. Relative positions of mandrel and drill collar at several angles on 360° circumferences, thereby proving the feasibility of the method. The method can provide a technical reference and basis for prototype production of directional rotary steering system [3].